2003
DOI: 10.1111/j.1479-8301.2003.00020.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predominance of Alzheimer type dementia in rural Japan

Abstract: Background:The aim of the present study was to estimate prevalence rates of dementia and its subtypes in the population aged 65 years or more in a rural area of Japan. Methods:A survey was conducted in Itoigawa, a city with 33 120 inhabitants in Niigata Prefecture, Japan. There were 7847 persons aged 65 years or older, and they comprised 23.4% of the total population. The first phase survey included questions on medical history, activities of daily living, psychiatric and behavioral symptoms and MMSE. When the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…After we reviewed 45 articles, 24 were excluded as they did not meet our eligibility criteria, and a total of 21 studies (9 in English and 12 in Japanese) [3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23] met the inclusion criteria. The search results are given in figure 1, and table 1 summarizes the results of the studies that met the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…After we reviewed 45 articles, 24 were excluded as they did not meet our eligibility criteria, and a total of 21 studies (9 in English and 12 in Japanese) [3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23] met the inclusion criteria. The search results are given in figure 1, and table 1 summarizes the results of the studies that met the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…The number of subjects varied from 497 in Miyagi Tajiri town in the eastern part of Japan in 1998 to 9,274 in Hokkaido in the northern part in 1986. The prevalence ranged from 3.0% to 8.8% (Nakamura et al, 2004) and no particular tendency of increasing or decreasing could be observed. It might be partly because there were not many programs and measures against dementia initiated by local governments before 2001.…”
Section: Introductionmentioning
confidence: 83%
“…The other 285 subjects did not participate in the second phase due to refusal, death, or as a result of moving to other communities. The details of the design and methods of sampling in the baseline survey have been described elsewhere [15, 16]. …”
Section: Methodsmentioning
confidence: 99%